Beta Adrenergic Receptor Stimulation Suppresses Cell Migration in Association with Cell Cycle Transition in Osteoblasts—Live Imaging Analyses Based on FUCCI System. Issue 2 (9th September 2015) - Katsumura, Sakie; Ezura, Yoichi; Izu, Yayoi; Shirakawa, Jumpei; Miyawaki, Atsushi; Harada, Kiyoshi; Noda, Masaki
<x xml:space="preserve">Abstract</x> Osteoporosis affects over 20 million patients in the United States. Among those, disuse osteoporosis is serious as it is induced by bed‐ridden conditions in patients suffering from aging‐associated diseases including cardiovascular, neurological, and malignant neoplastic diseases. Although the phenomenon that loss of mechanical stress such as bed‐ridden condition reduces bone mass is clear, molecular bases for the disuse osteoporosis are still incompletely understood. In disuse osteoporosis model, bone loss is interfered by inhibitors of sympathetic tone and adrenergic receptors that suppress bone formation. However, how beta adrenergic stimulation affects osteoblastic migration and associated proliferation is not known. Here we introduced a live imaging system, fluorescent ubiquitination‐based cell cycle indicator (FUCCI), in osteoblast biology and examined isoproterenol regulation of cell cycle transition and cell migration in osteoblasts. Isoproterenol treatment suppresses the levels of first entry peak of quiescent osteoblastic cells into cell cycle phase by shifting from G1/G0 to S/G2/M and also suppresses the levels of second major peak population that enters into S/G2/M. The isoproterenol regulation of osteoblastic cell cycle transition is associated with isoproterenol suppression on the velocity of migration. This isoproterenol regulation of migration velocity is cell cycle phase specific as it suppresses migration velocity of osteoblasts in G1 phase but not in G1/S nor in G2/M phase. Finally, these observations on isoproterenol regulation of osteoblastic migration and cell cycle transition are opposite to the PTH actions in osteoblasts. In summary, we discovered that sympathetic tone regulates osteoblastic migration in association with cell cycle transition by using FUCCI system. J. Cell. Physiol. 231: 496–504, 2016. © 2015 Wiley Periodicals, Inc.